Impaired decidual natural killer cell regulation of vascular remodelling in early human pregnancies with high uterine artery resistance - Fraser, Rupsha (John Wiley & Sons, Ltd, 2012)
During human pregnancy, natural killer (NK) cells accumulate in the maternal decidua, but their specific roles remain to be determined. Decidual NK (dNK) cells are present during trophoblast invasion and uterine spiral artery remodelling. These events are crucial for successful placentation and the provision of an adequate blood supply to the developing fetus. Remodelling of spiral arteries is impaired in the dangerous pregnancy complication pre-eclampsia. We studied dNK cells isolated from pregnancies at 9–14 weeks' gestation, screened by uterine artery Doppler ultrasound to determine resistance indices which relate to the extent of spiral artery remodelling. dNK cells were able to promote the invasive behaviour of fetal trophoblast cells, partly through HGF. Cells isolated from pregnancies with higher resistance indices were less able to do this and secreted fewer pro-invasive factors. dNK cells from pregnancies with normal resistance indices could induce apoptotic changes in vascular smooth muscle and endothelial cells in vitro, events of importance in vessel remodelling, partly through Fas signalling. dNK cells isolated from high resistance index pregnancies failed to induce vascular apoptosis and secreted fewer pro-apoptotic factors. We have modelled the cellular interactions at the maternal-fetal interface and provide the first demonstration of a functional role for dNK cells in influencing vascular cells. A potential mechanism contributing to impaired vessel remodelling in pregnancies with a higher uterine artery resistance is presented. These findings may be informative in determining the cellular interactions contributing to the pathology of pregnancy disorders where remodelling is impaired, such as pre-eclampsia. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.